2020
DOI: 10.1038/s41541-020-00257-5
|View full text |Cite
|
Sign up to set email alerts
|

Baseline mapping of severe fever with thrombocytopenia syndrome virology, epidemiology and vaccine research and development

Abstract: Severe fever with thrombocytopenia syndrome virus (SFTSV) is a newly emergent tick-borne bunyavirus first discovered in 2009 in China. SFTSV is a growing public health problem that may become more prominent owing to multiple competent tick-vectors and the expansion of human populations in areas where the vectors are found. Although tick-vectors of SFTSV are found in a wide geographic area, SFTS cases have only been reported from China, South Korea, Vietnam, and Japan. Patients with SFTS often present with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 136 publications
(319 reference statements)
0
30
0
Order By: Relevance
“…These aberrantly altered parameters are indicative of pathological lesions in the heart, kidney, liver, and coagulation systems of SFTS positive patients. In SFTS, hepatocytes were found to be not infected with SFTSV, while several SFTSV-NP antigen-positive cells were detected in the liver [ 19 , 20 ]. In this view, it is demonstrated that in SFTS positive patients, the liver damage might be due to a subordinate pathological event rather than due to direct destruction caused by SFTSV.…”
Section: Discussionmentioning
confidence: 99%
“…These aberrantly altered parameters are indicative of pathological lesions in the heart, kidney, liver, and coagulation systems of SFTS positive patients. In SFTS, hepatocytes were found to be not infected with SFTSV, while several SFTSV-NP antigen-positive cells were detected in the liver [ 19 , 20 ]. In this view, it is demonstrated that in SFTS positive patients, the liver damage might be due to a subordinate pathological event rather than due to direct destruction caused by SFTSV.…”
Section: Discussionmentioning
confidence: 99%
“…Although tick-vectors of SFTS are found in a wide geographic area, SFTS has only been reported from limited Southeast Asia such as China, South Korea, Vietnam, and Japan. However, it may become more prominent in the future due to the increased international communication and the expansion of the areas where the vectors can live [8]. Crimean-Congo hemorrhagic fever is another tick-borne viral hemorrhagic fever currently found in Europe, Asia, Africa, the Middle East, and the Indian subcontinent.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The causative agent of SFTS is a novel phlebovirus in the Bunyaviridae family, which was named SFTS virus (SFTSV) ( Yu et al, 2011 ). Since its initial discovery, SFTS has been epidemic in more than 20 provinces in China, which has threatened the health of Chinese people seriously ( Guo et al, 2016 ; Zhan et al, 2017 ; Bopp et al, 2020 ; Li et al, 2021 ). Anhui province has shown a higher disease burden of SFTS ( Zhan et al, 2017 ; Bopp et al, 2020 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since its initial discovery, SFTS has been epidemic in more than 20 provinces in China, which has threatened the health of Chinese people seriously ( Guo et al, 2016 ; Zhan et al, 2017 ; Bopp et al, 2020 ; Li et al, 2021 ). Anhui province has shown a higher disease burden of SFTS ( Zhan et al, 2017 ; Bopp et al, 2020 ; Li et al, 2021 ). Besides China, SFTSV infections have also been confirmed in Japan, South Korea, Vietnam, and Pakistan ( Li, 2015 ; Tran et al, 2019 ; Bopp et al, 2020 ; Miao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation